Third World education : quality and equality - Welch, Anthony R. (Garland reference library of social science ;, 2000)
This book debunks the argument that quality in education can only be achieved by limiting, or trading off, equality. This book argues that any worthy definition of quality education must include the interest of the underprivileged.